Deodorizing fiber and preparation method thereof as well as deodorizing fabric and preparation method thereof
Through the combination of active clay and titanium dioxide, anti-odor fibers with bactericidal and anti-bacterial functions were prepared. Through knitting tissue and post-organization process, the problem of insufficient anti-bacterial and odor deodorization performance of textile fabrics was solved, achieving efficient odor reduction and anti-bacterial prevention. Moldy effect.
Patent Information
- Application Number
- CN202310822775.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-05
- Publication Date
- 2025-01-07
AI Technical Summary
Existing textile fabrics have shortcomings in antibacterial and deodorizing properties, especially during high temperatures or strenuous exercise, and bacteria grow, affecting the quality of life.
Active clay and titanium dioxide are used as key components of deodorization fibers. By mixing, dispersing, grinding and spinning, deodorization fibers with bactericidal and antibacterial functions are prepared, and deodorization fabrics are prepared through knitting tissue and post-organization process.
It significantly improved the anti-odor properties of odor-depressing fibers and the anti-bacterial and anti-molding effect of fabrics. The inhibition rate of Staphylococcus aureus, E. coli and Candida albicans reached 89.3%, 90.8% and 87.1% and the anti-mold level reached level 1. The above can reduce odor substances and provide good hygiene functions.
Smart Images

Figure CN119265725A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of textiles, and in particular to a deodorizing fiber and a preparation method thereof, and a deodorizing fabric and a preparation method thereof. Background Art
[0002] With the development of society and the improvement of people's living standards, people are paying more and more attention to health and wellness textiles. However, most textile fabrics on the market currently have obvious defects, mainly in terms of antibacterial and deodorizing performance. Especially in the summer when the temperature is high or during strenuous exercise, the human body is prone to sweating, which leads to odor. At the same time, these fabrics will be contaminated with sweat, sebum and other human secretions when they come into contact with the human body, becoming a breeding ground for bacteria and pathogenic microorganisms, bringing inconvenience to people's quality of life. Among them, the deodorizing performance of the fabric is closely related to the fibers in the fabric.
[0003] Therefore, in order to meet people's high requirements for the hygiene function of textiles, the textile industry urgently needs to improve the deodorizing performance of fibers in fabrics to meet market demand and obtain huge potential opportunities. Summary of the invention
[0004] The invention provides a deodorizing fiber and a preparation method thereof, and a deodorizing fabric and a preparation method thereof.
[0005] The method for preparing the deodorizing fiber according to the embodiment of the present invention comprises:
[0006] Providing activated clay and titanium dioxide, and mixing the activated clay and the titanium dioxide in a mass ratio of 2:1 to 4:1 to obtain a solid mixture;
[0007] Dispersing the solid mixture with deionized water in a mass ratio of 1:3 to 1:5, and adding a dispersant, a thickener and a defoamer to obtain a first dispersed system;
[0008] Grinding the first dispersion system to a particle size of D90≤1.656 μm to obtain a second dispersion system;
[0009] Providing a cellulose spinning solution and a pore-forming agent, and adding the second dispersed system and the pore-forming agent to the cellulose spinning solution to obtain a blended spinning solution;
[0010] The blended spinning solution is introduced into a coagulation bath for spinning and forming to obtain deodorizing fibers.
[0011] In the preparation method of the deodorizing fiber of the embodiment of the present invention, titanium dioxide is a photocatalyst material, which can produce strong oxidizing substances under light irradiation, and can achieve the decomposition of organic matter, so that the fiber has a bactericidal and antibacterial effect, so that the deodorizing fiber has good deodorizing performance; activated white clay can enhance the adsorption of the deodorizing fiber to odor and odor carriers, thereby further enhancing the bactericidal and antibacterial function of the deodorizing fiber, thereby further improving the deodorizing performance of the deodorizing fiber; by dispersing the solid mixture and deionized water in an appropriate mass ratio, the deodorant can be evenly dispersed in the water. This helps to effectively disperse the deodorant into the fiber material and improve the deodorizing performance of the deodorizing fiber.
[0012] In addition, by grinding the particles to a smaller particle size, the fiber surface area is relatively increased. The increase in fiber surface area can provide more contact surfaces, thereby increasing the chances of contact and adsorption with odor molecules in the environment, which can help improve the fiber material's ability to adsorb odors, thereby improving the deodorizing performance; the addition of pore-forming agents and coagulation baths makes the deodorizing fibers present a hollow structure, so that the surface and interior of the deodorizing fibers contain a large number of holes, thereby further enhancing the bactericidal and antibacterial functions of the deodorizing fibers, thereby further improving the deodorizing performance of the deodorizing fibers.
[0013] In certain embodiments, in the first dispersed system, the mass fraction of the dispersant is 1.0% to 2.0%, the mass fraction of the thickener is 0.5% to 1.5%, and the mass fraction of the defoaming agent is 1.0% to 2.5%.
[0014] In certain embodiments, the dispersant includes at least one of sodium naphthalenesulfonate, sodium dodecylbenzenesulfonate, or sodium hexametaphosphate.
[0015] In certain embodiments, the thickener includes at least one of sodium hydroxyethyl cellulose, sodium carboxymethyl cellulose, sodium carboxyethyl cellulose, or hydroxypropyl methyl cellulose.
[0016] In certain embodiments, the cellulose spinning solution comprises, by mass fraction, 8.86% to 9.55% methyl cellulose and 6.21% to 7.10% sodium hydroxide.
[0017] In certain embodiments, the cellulose spinning solution is prepared by the following steps:
[0018] Providing cellulose sulfonates;
[0019] The cellulose sulfonate is dissolved, and in the process of dissolving the cellulose sulfonate, a denaturant accounting for 2.0 wt% to 3.5 wt% of the cellulose methyl content is added to obtain the cellulose spinning stock solution.
[0020] In certain embodiments, the denaturant includes at least one of polyethylene glycol, fatty alcohol polyoxyethylene ether, or fatty amine polyoxyethylene ether.
[0021] In certain embodiments, the mass fraction of the solid mixture to the methyl cellulose is 8.0% to 15.0%, and the mass fraction of the pore former to the methyl cellulose is 5.0% to 8.0%.
[0022] In certain embodiments, the concentration of sulfuric acid in the coagulation bath is 95 g / L to 110 g / L, the concentration of sodium sulfate is 290 g / L to 330 g / L, and the concentration of aluminum sulfate is 12.5 g / L to 16.5 g / L.
[0023] The deodorizing fiber according to the embodiment of the present invention is prepared by the method for preparing the deodorizing fiber according to any one of the above embodiments.
[0024] The method for preparing the deodorizing fabric according to the embodiment of the present invention comprises:
[0025] Providing a first yarn, a second yarn and a third yarn, wherein the first yarn comprises the deodorizing fiber described in the above embodiment;
[0026] The first yarn, the second yarn and the third yarn are knitted into a plurality of knitted structures, each of the knitted structures has 12 loops as a cycle, wherein the first yarn is used in the 1st, 4th, 5th, 7th, 9th and 10th loops, the second yarn is used in the 2nd, 8th and 11th loops, and the third yarn is used in the 3rd, 6th and 12th loops, and the coil lengths of the first yarn, the second yarn and the third yarn are all 15 cm / 100 loops to 30 cm / 100 loops, so as to obtain a first deodorizing sub-fabric;
[0027] The first deodorizing sub-fabric is subjected to a post-finishing process to obtain the deodorizing fabric.
[0028] In some embodiments, the post-finishing process of the first deodorizing sub-fabric comprises:
[0029] adding the first deodorizing sub-fabric into a first finishing liquid to obtain a second deodorizing sub-fabric, wherein the first finishing liquid comprises tea polyphenols and chlorogenic acid;
[0030] adding the second deodorizing sub-fabric into a second finishing liquid to obtain a third deodorizing sub-fabric, wherein the second finishing liquid comprises at least one of a zinc finishing agent or a copper finishing agent;
[0031] Dehydrating or drying the third deodorizing sub-fabric;
[0032] The deodorizing sub-fabric is subjected to a qualitative softening process after being dehydrated or dried to obtain the deodorizing fabric.
[0033] In certain embodiments, the concentration of the tea polyphenols is 10.0 g / L to 25.0 g / L, and the concentration of the chlorogenic acid is 10.0 g / L to 16.0 g / L.
[0034] In certain embodiments, the zinc finishing agent includes at least one of zinc sulfate, zinc chloride or zinc acetate, and the copper finishing agent includes at least one of copper ammonia solution, copper sulfate or copper chloride.
[0035] The deodorizing fabric according to the embodiment of the present invention is prepared by the preparation method of the deodorizing fabric according to any one of the above embodiments.
[0036] Additional aspects and advantages of the present invention will be given in part in the following description and in part will be obvious from the following description, or will be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] The above and / or additional aspects and advantages of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0038] Figure 1 It is a schematic flow chart of a method for preparing deodorizing fiber according to one embodiment of the present invention;
[0039] Figure 2 It is a schematic flow chart of a method for preparing deodorizing fiber according to one embodiment of the present invention;
[0040] Figure 3 It is a schematic flow chart of a method for preparing a deodorizing fabric according to an embodiment of the present invention;
[0041] Figure 4 It is a schematic flow chart of a method for preparing a deodorizing fabric according to one embodiment of the present invention. DETAILED DESCRIPTION
[0042] The embodiments of the present invention are described in detail below, examples of which are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements having the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present invention, and cannot be understood as limiting the present invention.
[0043] In the description of the present invention, it should be understood that the terms "center", "longitudinal", "lateral", "length", "width", "thickness", "up", "down", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inside", "outside", "clockwise", "counterclockwise" and the like indicate positions or positional relationships based on the positions or positional relationships shown in the accompanying drawings, and are only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first" and "second" are only used for descriptive purposes, and cannot be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of the present invention, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.
[0044] In the description of the present invention, it should be noted that, unless otherwise clearly specified and limited, the terms "installed", "connected", and "connected" should be understood in a broad sense, for example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection, an electrical connection, or mutual communication; it can be a direct connection, or an indirect connection through an intermediate medium, it can be the internal connection of two elements or the interaction relationship between two elements. For ordinary technicians in this field, the specific meanings of the above terms in the present invention can be understood according to specific circumstances.
[0045] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may include that the first and second features are in direct contact, or may include that the first and second features are not in direct contact but are in contact through another feature between them. Moreover, a first feature being "above", "above" and "above" a second feature includes that the first feature is directly above and obliquely above the second feature, or simply indicates that the first feature is higher in level than the second feature. A first feature being "below", "below" and "below" a second feature includes that the first feature is directly below and obliquely below the second feature, or simply indicates that the first feature is lower in level than the second feature.
[0046] The disclosure below provides many different embodiments or examples to realize different structures of the present invention. In order to simplify the disclosure of the present invention, the parts and settings of specific examples are described below. Of course, they are only examples, and the purpose is not to limit the present invention. In addition, the present invention can repeat reference numbers and / or reference letters in different examples, and this repetition is for the purpose of simplicity and clarity, which itself does not indicate the relationship between the various embodiments and / or settings discussed. In addition, the present invention provides various specific examples of processes and materials, but those of ordinary skill in the art can be aware of the application of other processes and / or the use of other materials.
[0047] See also Figure 1 The method for preparing the deodorizing fiber according to the embodiment of the present invention comprises:
[0048] S10, providing activated clay and titanium dioxide, and mixing the activated clay and titanium dioxide in a mass ratio of 2:1 to 4:1 to obtain a solid mixture;
[0049] S20, dispersing the solid mixture with deionized water in a mass ratio of 1:3 to 1:5, and adding a dispersant, a thickener and a defoamer to obtain a first dispersed system;
[0050] S30, grinding the particle size of the first dispersed system to D90≤1.656 μm to obtain a second dispersed system;
[0051] S40, providing a cellulose spinning solution and a pore-forming agent, and adding the second dispersion system and the pore-forming agent to the cellulose spinning solution to obtain a blended spinning solution;
[0052] S50, introducing the blended spinning solution into a coagulation bath for spinning and forming to obtain deodorizing fibers.
[0053] In the preparation method of the deodorizing fiber of the embodiment of the present invention, titanium dioxide is a photocatalyst material, which can produce strong oxidizing substances under light irradiation, and can achieve the decomposition of organic matter, so that the fiber has a bactericidal and antibacterial effect, so that the deodorizing fiber has good deodorizing performance; activated white clay can enhance the adsorption of the deodorizing fiber to odor and odor carriers, thereby further enhancing the bactericidal and antibacterial function of the deodorizing fiber, thereby further improving the deodorizing performance of the deodorizing fiber; by dispersing the solid mixture and deionized water in an appropriate mass ratio, the deodorant can be evenly dispersed in the water. This helps to effectively disperse the deodorant into the fiber material and improve the deodorizing performance of the deodorizing fiber.
[0054] In addition, by grinding the particles to a smaller particle size, the fiber surface area is relatively increased. The increase in fiber surface area can provide more contact surfaces, thereby increasing the chances of contact and adsorption with odor molecules in the environment, which can help improve the fiber material's ability to adsorb odors, thereby improving the deodorizing performance; the addition of pore-forming agents and coagulation baths makes the deodorizing fibers present a hollow structure, so that the surface and interior of the deodorizing fibers contain a large number of holes, thereby further enhancing the bactericidal and antibacterial functions of the deodorizing fibers, thereby further improving the deodorizing performance of the deodorizing fibers.
[0055] Specifically, both activated clay and titanium dioxide can be raw materials sold on the market. The mass ratio of activated clay and titanium dioxide can be 2:1-3.5:1, 2.5:1-3.5:1, 3:1-3.5:1, 3:1-3.5:1, 3:1-4:1, 3.5:1-4:1, etc.; the mass ratio of activated clay and titanium dioxide can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, etc. The ratio of activated clay and titanium dioxide affects the specific surface area and reaction activity of the solid mixture. An appropriate mass ratio can provide a larger specific surface area, promote the interaction between titanium dioxide and activated clay, enhance the adsorption and catalytic effects, and thus improve the deodorizing performance of the fiber.
[0056] The mass ratio of the solid mixture to deionized water can be 1:3-1:4.5, 1:3.5-1:4.5, 1:3.5-1:4, 1:3.5-1:5, 1:4-1:5, etc.; the mass ratio of the solid mixture to deionized water can be 1:3, 1:3.5, 1:4, 1:4.5, 1:5, etc.
[0057] The solid mixture is mixed with deionized water in a certain mass ratio to form a suspension or dispersion system. The appropriate mass ratio helps to provide proper dispersibility, that is, the solid particles are evenly dispersed in the water to avoid agglomeration and precipitation. This ensures that the activated clay and titanium dioxide are fully exposed to the water to exert their adsorption and catalytic properties. The mass ratio of the solid mixture to deionized water can also affect the interfacial interaction between the solid and water. The appropriate mass ratio can promote the contact and interaction between the solid surface and water, increase the chance of adsorption and catalytic reaction, and improve the deodorization performance.
[0058] By using a first dispersion system, solid particles can be dispersed into a continuous phase (such as a solution or suspension) of the fiber material so that they are evenly distributed throughout the fiber. The first dispersion system can ensure the uniform distribution of solid particles in the fiber material, which is critical to achieving a consistent deodorizing effect.
[0059] In certain embodiments, in the first dispersed system, the mass fraction of the dispersant is 1.0% to 2.0%, the mass fraction of the thickener is 0.5% to 1.5%, and the mass fraction of the defoaming agent is 1.0% to 2.5%.
[0060] For example, the mass fraction of the dispersant can be 1.0% to 1.9%, 1.1% to 1.9%, 1.2% to 1.8%, 1.4% to 1.5%, 1.4% to 2.0%, etc.; the mass fraction of the dispersant can be 1.0%, 1.2%, 1.4%, 1.5%, 2.0%, etc.
[0061] The mass fraction of the thickener can be 0.5% to 1.4%, 0.6% to 1.4%, 0.6% to 1.2%, 0.8% to 1.0%, 0.8% to 1.5%, etc.; the mass fraction of the thickener can be 0.5%, 0.6%, 1.0%, 1.2%, 1.5%, etc.
[0062] The mass fraction of the defoaming agent can be 1.0% to 2.4%, 1.2% to 2.4%, 1.5% to 2.0%, 1.5% to 2.5%, 2.0% to 2.5%, etc.; the mass fraction of the defoaming agent can be 1.0%, 1.2%, 1.5%, 2.0%, 2.5%, etc.
[0063] Within these parameter ranges, the properties of the first dispersed system can be optimized, thereby improving the contact and reaction effects between the fiber and the solid mixture, thereby improving the consistency and reliability of the deodorizing effect of the fiber.
[0064] Specifically, the role of the dispersant is to improve the dispersibility of solid particles in liquids and prevent agglomeration and precipitation. Appropriate dispersants can evenly disperse solid particles in water, improve the adsorption and catalytic effects of solid particles, and thus help improve the deodorizing performance of the fiber.
[0065] In some embodiments, the dispersant includes at least one of sodium naphthalenesulfonate, sodium dodecylbenzenesulfonate or sodium hexametaphosphate. Selecting the above materials as dispersants can provide higher adsorption performance or stronger dispersion stability.
[0066] Specifically, sodium naphthalenesulfonate is an anionic surfactant with good dispersing and wetting properties. It can form a negatively charged adsorption layer on the surface of solid particles, causing electrostatic repulsion between particles, reducing agglomeration, and thus improving dispersion performance.
[0067] Sodium dodecylbenzene sulfonate is also an anionic surfactant with good dispersing and wetting properties. It can form an adsorption layer on the surface of solid particles, improve the interaction between particles, and prevent agglomeration and precipitation.
[0068] Sodium hexametaphosphate is a multifunctional ionic surfactant with strong dispersibility and wettability. It can form micelle structure in water, encapsulate solid particles in micelles, and prevent agglomeration and precipitation.
[0069] The function of thickener is to increase the viscosity and consistency of the dispersion system, making it more suspendable and stable. Appropriate thickener can make solid particles more stable in the dispersion system, prevent solid particles from settling and stratifying, and help improve the deodorizing effect.
[0070] In certain embodiments, the thickener includes at least one of sodium hydroxyethyl cellulose, sodium carboxymethyl cellulose, sodium carboxyethyl cellulose, or hydroxypropyl methyl cellulose.
[0071] Sodium hydroxyethyl cellulose, sodium carboxymethyl cellulose, sodium carboxyethyl cellulose and hydroxypropyl methyl cellulose all have good thickening properties, which can increase the viscosity and viscosity of the dispersion system, improve the suspension and stability of solid particles, thereby achieving the uniformity and fluidity of the dispersion system, and further improving the deodorizing performance of the fiber.
[0072] Specifically, sodium hydroxyethyl cellulose is a water-soluble polymer with good thickening and stabilizing properties. It can form a solution with high viscosity in water and has good stability to changes in temperature and salinity. The reason for choosing sodium hydroxyethyl cellulose as a thickener is that it can effectively increase the viscosity of the dispersed system, giving it better suspension and fluidity.
[0073] Sodium carboxymethyl cellulose is an anionic surfactant with thickening and dispersing effects. It forms a viscous solution after dissolving in water, and can be adsorbed on the surface of solid particles to form a stable micelle structure to prevent solid particles from agglomerating. The reason for choosing sodium carboxymethyl cellulose as a thickener is that it can effectively increase the viscosity and stability of the dispersion system and improve the uniform dispersion of solid particles.
[0074] Sodium carboxyethyl cellulose is an anionic surfactant with thickening and dispersing properties. It forms a high-viscosity solution in water and can effectively increase the viscosity and stability of the dispersion system. The reason for choosing sodium carboxyethyl cellulose as a thickener is that it can improve the rheological properties of the dispersion system and improve the suspension and uniformity of the dispersion system.
[0075] Hydroxypropyl methylcellulose is a synthetic cellulose derivative with good solubility and thickening properties. It forms a viscous solution after dissolving in water, which can effectively increase the viscosity and viscosity of the dispersion system. The reason for choosing hydroxypropyl methylcellulose as a thickener is that it can increase the viscosity of the dispersion system and improve the suspension and stability of solid particles.
[0076] The function of defoamer is to reduce or prevent the formation and aggregation of bubbles in the dispersion system. Appropriate defoamer can reduce the presence of bubbles, avoid the interference of bubbles on solid particles, and improve the deodorization performance. The defoamer can be at least one of ZY-T6911 defoamer, ZY-F609 high temperature resistant defoamer, and ZY-T69113 silicone polyether defoamer. These types of defoamers have strong performance.
[0077] After obtaining the first dispersed system, a sand mill can be used to grind the particles in the first dispersed system under water circulation cooling conditions, so that in the particle size distribution, 90% of the particle diameters (ie, D90) do not exceed 3 micrometers (μm).
[0078] The temperature of the water circulation cooling can be 10°C to 20°C, and the particle size refers to the size of the particles. The significance of grinding the particle size of the dispersion system to D90≤3μm is that by reducing the size of the particles, the specific surface area of the particles can be increased, the contact area between the particles and other substances can be increased, and the uniformity and stability of the dispersion system can be improved. Furthermore, the smaller particle size can also increase the surface area of the second dispersion system, improve the release efficiency of the active ingredients, and thus enhance the deodorizing performance of the deodorizing fiber.
[0079] The falling ball viscosity of the second dispersed system can be 20s-34s, 22s-34s, 25s-32s, 25s-35s, 32s-35s, etc.; the falling ball viscosity of the second dispersed system can be 20s, 22s, 25s, 32s, 35s, etc. Within this range, the stability and particle concentration of the second dispersed system can meet the requirements.
[0080] Falling ball viscosity is the viscosity of a liquid measured in the presence of suspended particles in a second dispersed system. It is determined by releasing a small ball (usually a metal or glass ball) into the second dispersed system and measuring the speed at which the ball falls in the liquid. According to Stokes' law, the viscosity is proportional to the falling speed, so the viscosity of the second dispersed system can be estimated by measuring the falling speed of the ball.
[0081] Further, a high falling ball viscosity indicates a strong interaction between the suspended particles and the continuous phase, resulting in an increase in viscosity. A low falling ball viscosity may mean that there are fewer particles in the dispersion or that the dispersion is better dispersed. By monitoring the changes in falling ball viscosity, the stability of the secondary dispersion can be assessed and necessary adjustments and optimizations can be made.
[0082] The concentration of particles in a dispersed system can be estimated from the falling ball viscosity measurement results. According to Stokes' law, viscosity is proportional to particle concentration. Therefore, by comparing the falling ball viscosity at different concentrations, the change in particle concentration can be inferred.
[0083] In certain embodiments, the cellulose spinning solution comprises, by mass fraction, 8.86% to 9.55% of methyl cellulose and 6.21% to 7.10% of sodium hydroxide.
[0084] For example, the mass fraction of type A cellulose in the home can be 8.86%~9.54%, 8.88%~9.52%, 8.90%~9.50%, 8.95%~9.54%, 8.90%~9.54%, etc.; the mass fraction of type A cellulose can be 8.86%, 8.88%, 8.90%, 8.95%, 8.90%~9.54%, etc.
[0085] The mass fraction of sodium hydroxide can be 6.21% to 7.05%, 6.30% to 7.05%, 6.40% to 7.00%, 6.50% to 6.80%, 6.50% to 7.10%, etc.; the mass fraction of sodium hydroxide can be 6.21%, 6.30%, 6.40%, 6.50%, 7.10%, etc.
[0086] The falling ball viscosity of the cellulose spinning solution can be 76s-115s, the maturity (10% NH4Cl value) can be 20mL-32mL, the viscose esterification degree can be 58-82, and the viscose sulfur content can be 2.25%-2.61%.
[0087] Please refer to Figure 2 In some embodiments, the cellulose spinning solution (step S40) is prepared by the following steps:
[0088] S41, providing cellulose sulfonate;
[0089] S42, dissolving cellulose sulfonate, adding a denaturant accounting for 2.0wt% to 3.5wt% of type A cellulose in the process of dissolving the cellulose sulfonate to obtain a cellulose spinning solution, adding a binary dispersion system and a pore-forming agent to the cellulose spinning solution to obtain a blended spinning solution.
[0090] It is understood that cellulose sulfonate is a substance that is relatively insoluble in solvents and has a low solubility. By adding a denaturant, the solubility of cellulose sulfonate can be improved, and its dispersion and dissolution in the solvent can be promoted. The role of the denaturant is to destroy the interaction between cellulose sulfonate molecules and reduce the degree of aggregation in the solvent, thereby increasing the solubility and dissolution rate.
[0091] Specifically, the content of the denaturant can be 2.0wt% to 3.3wt%, 2.2wt% to 3.3wt%, 2.5wt% to 3.0wt%, 2.5wt% to 3.5wt%, 3.0wt% to 3.5wt%, etc.; the content of the denaturant can be 2.0wt%, 2.2wt%, 2.5wt%, 3.0wt%, 3.5wt%, etc. An appropriate content of the denaturant is more efficient in improving the solubility of the cellulose sulfonate.
[0092] In certain embodiments, the denaturant includes at least one of polyethylene glycol, fatty alcohol polyoxyethylene ether, or fatty amine polyoxyethylene ether, wherein the model of polyethylene glycol may be PEG-1500.
[0093] Compounds such as polyethylene glycol, fatty alcohol polyoxyethylene ether and fatty amine polyoxyethylene ether have good solubility in common solvents and can interact with cellulose sulfonate molecules to promote their dispersion and dissolution in the solvent.
[0094] In certain embodiments, the mass fraction of the solid mixture to the methyl cellulose is 8.0% to 15.0%, and the mass fraction of the pore-forming agent to the methyl cellulose is 5.0% to 8.0%.
[0095] For example, the mass fraction of the solid mixture in type methyl cellulose can be 8.0% to 14.0%, 8.5% to 14.0%, 9.0% to 12.0%, 12.0% to 15.0%, 9.0% to 15.0%, etc.; the mass fraction of the solid mixture in type methyl cellulose can be 8.0%, 8.5%, 9.0%, 12.0%, 15.0%, etc.
[0096] The mass fraction of the pore-forming agent in the type methyl cellulose can be 5.0% to 7.5%, 5.5% to 7.5%, 6.0% to 7.0%, 7.0% to 8.0%, 6.0% to 8.0%, etc.; the mass fraction of the pore-forming agent in the type methyl cellulose can be 5.0%, 5.5%, 6.0%, 7.0%, 8.0%, etc.
[0097] Within these parameter ranges, the molded deodorizing fiber can present a hollow structure, and the pore-forming agent will decompose during the molding process and generate carbon dioxide overflow, so that the surface and interior of the deodorizing fiber contain a large number of holes, increasing the adsorption amount of subsequent functional additives (such as chlorogenic acid and tea polyphenols with antibacterial and anti-mildew effects). Moreover, the adsorbed functional substances can be complexed with each other and with the deodorizing fiber, which improves stability and reduces the loss of functional additives during subsequent use, making the deodorizing fiber more functional. Lasting.
[0098] In certain embodiments, the concentration of sulfuric acid in the coagulation bath is 95 g / L to 110 g / L, the concentration of sodium sulfate is 290 g / L to 330 g / L, and the concentration of aluminum sulfate is 12.5 g / L to 16.5 g / L.
[0099] For example, the concentration of sulfuric acid can be 95g / L~108g / L, 98g / L~108g / L, 99g / L~105g / L, 100g / L~105g / L, 105g / L~110g / L, etc.; the concentration of sulfuric acid can be 95g / L, 98g / L, 99g / L, 100g / L, 110g / L, etc.
[0100] The concentration of sodium sulfate can be 290g / L~320g / L, 295g / L~325g / L, 300g / L~320g / L, 320g / L~330g / L, 300g / L~330g / L, etc.; the concentration of sodium sulfate can be 290g / L, 295g / L, 300g / L, 320g / L, 330g / L, etc.
[0101] The concentration of aluminum sulfate can be 12.5g / L~16.0g / L, 13.0g / L~16.0g / L, 13.5g / L~15.5g / L, 15.5g / L~16.5g / L, 13.5g / L~16.5g / L, etc.; the concentration of aluminum sulfate can be 12.5g / L, 13.0g / L, 13.5g / L, 15.5g / L, 16.5g / L, etc.
[0102] Within these parameter ranges, the deodorizing fiber obtained has good deodorizing performance.
[0103] Specifically, the coagulation bath is a chemical solution used to coagulate and solidify the spinning solution during the spinning process. Its main function is to convert the cellulose dissolved in the spinning solution into solid cellulose fibers during the spinning process, and to give the fibers a certain strength and structural stability.
[0104] Among them, sulfuric acid and sodium sulfate are acidic substances, which can react with the cellulose dissolved in the spinning solution to cause the coagulation and solidification of cellulose. In an acidic environment, cross-linking and rearrangement occur between cellulose molecules to form crystalline areas of cellulose, thereby forming a fiber structure of cellulose.
[0105] Aluminum sulfate is a hardener that can react with cellulose in the spinning solution to form a more compact structure. Aluminum sulfate has a condensation effect and can react with cellulose molecules to form a cross-linked structure, increasing the strength and stability of cellulose fibers.
[0106] The composition and concentration of sulfuric acid, sodium sulfate and aluminum sulfate in the coagulation bath can be adjusted as needed to control the fiber formation process and properties. They can affect the structure, morphology, strength, porosity and other properties of the fiber, thereby achieving control and regulation of the spinning process.
[0107] The blended spinning solution is spun through the adjusted coagulation bath, and the primary filament bundle is drawn to obtain the formed filament bundle. The special spinning forming process and pore-forming agent are used to make the prepared cellulose fiber present a hollow structure, and there are more holes on the surface and inside, which increases the active area of the adsorbent activated clay, and facilitates the subsequent functional modification of the fabric. After drawing, cutting, and using the mild desulfurization process, oiling process, drying process, and finally opening treatment, the deodorizing fiber is obtained.
[0108] Among them, the temperature of the adjusted coagulation bath can be 45℃~50℃; in the desulfurization process, Na 2 SO 3 The concentration can be 6.0g / L~9.5g / L, and the temperature can be 60℃~85℃; in the oiling process, the concentration of the oil bath can be 3.0g / L~5.5g / L, and the temperature can be 50℃~70℃; in the drying process, steam drying can be used, the drying temperature can be 110℃~130℃, and the moisture regain of the deodorizing fiber after drying can be 9%~12%.
[0109] The deodorizing fiber according to the embodiment of the present invention is prepared by the preparation method of the deodorizing fiber according to any of the above embodiments.
[0110] In the deodorizing fiber of the embodiment of the present invention, titanium dioxide and activated white clay can provide bactericidal and antibacterial functions, thereby enhancing the deodorizing performance of the deodorizing fiber, and, through subsequent dispersion, grinding and pore-forming agent addition, the adsorption capacity of the deodorizing fiber for odor molecules is enhanced, thereby improving the deodorizing performance of the deodorizing fiber.
[0111] Please refer to Figure 3 The method for preparing the deodorizing fabric according to the embodiment of the present invention comprises:
[0112] S60, providing a first yarn, a second yarn and a third yarn, wherein the first yarn includes the deodorizing fiber of the above embodiment;
[0113] S70, knitting the first yarn, the second yarn and the third yarn into a plurality of knitted structures, each knitted structure having 12 loops as a cycle, wherein the first yarn is used in the first, fourth, fifth, seventh, ninth and tenth loops, the second yarn is used in the second, eighth and eleventh loops, and the third yarn is used in the third, sixth and twelfth loops, and the coil lengths of the first yarn, the second yarn and the third yarn are all 15 cm / 100 loops to 30 cm / 100 loops, so as to obtain a first deodorizing sub-fabric;
[0114] S80, performing a post-finishing process on the first deodorizing sub-fabric to obtain a deodorizing fabric.
[0115] The post-finishing can increase the functional durability and functionality of the deodorizing fiber of the deodorizing fabric. The fabric of the embodiment of the present invention has good deodorizing performance, which is specifically manifested as an inhibition rate of ≥89.3% against Staphylococcus aureus, an inhibition rate of ≥90.8% against Escherichia coli, and an inhibition rate of ≥87.1% against Candida albicans. The above parameters are measured according to GBT20944.3-2008 "Evaluation of Antibacterial Properties of Textiles Part 3: Oscillation Method"; the mildew resistance level can reach level 1 or above; its reduction rate of ammonia is ≥89.1%, the reduction rate of trimethylamine is ≥86.5%, and the reduction rate of isovaleric acid is ≥89.3%; the ultraviolet protection factor is ≥60; the drip diffusion time is ≤2.8s, and the evaporation rate is ≥0.19g / h.
[0116] Specifically, the first yarn, the second yarn and the third yarn can be prepared through the processes of opening and cleaning, combing, drawing, roving and spinning. In the processes of opening and cleaning and combing, the fibers used to prepare the yarn are prepared according to a certain mass ratio, the beater speed can be set to 720rpm / min to 880rpm / min, the plucking machine operating efficiency can be 92% to 95%, the sliver delivery speed can be 55m / min to 65m / min, and the raw sliver weight can be 12g / 5m to 16g / 5m.
[0117] In the drawing process, two drawing passes are adopted, in which the number of roots combined in the first drawing can be 8, and the total drafting multiple can be 8.1 times to 8.8 times; the number of roots combined in the second drawing can be 7, and the total drafting multiple can be 7.6 times to 8.1 times; in the roving process, the roller spacing can be 10mm*26mm*36mm, the total drafting multiple can be 8.7 to 9.0 times, the twist coefficient can be 70 to 80, and the sliver dryness CV (Coefficient of Variation of Sliver Dryness) can be 4.3% to 4.9%.
[0118] In the spinning process, the roller spacing can be 17mm*38mm, the total drafting multiple can be 25 times to 35 times, the twist can be 80 twists / 10cm to 100 twists / 10cm, and the twist coefficient can be 360 to 398.
[0119] For the first yarn (S twist direction), it includes the deodorizing fiber described in the above embodiment and Instant deodorizing fiber, deodorizing fiber and The instant deodorizing fiber can be uniformly mixed in a mass ratio of 40-50%:60-50%, and then prepared by the above-mentioned yarn preparation process.
[0120] For the second yarn (Z twist direction), it can be obtained by uniformly mixing nylon 6 staple fiber or nylon 66 staple fiber and antibacterial cotton fiber in a mass ratio of 30% to 40%: 60% to 70%, and then using the above-mentioned yarn preparation process.
[0121] For the third yarn (Z twist), it can be used The quick-drying cotton and the polylactic acid fiber are uniformly mixed in a mass ratio of 50-60%:50-40%, and then the mixture is prepared by the above-mentioned yarn preparation process.
[0122] Among them, nylon 6 staple fiber and nylon 66 fiber can be commercially available products or customized products. Since the thermal conductivity of nylon fiber reaches 0.244-0.337, the thermal conductivity is relatively high. Compared with other fibers, nylon fiber can conduct heat quickly and give a cool feeling. At the same time, nylon fiber has good wear resistance.
[0123] Antibacterial cotton fibers may include Antiviral cotton, Chitosan antibacterial cotton, sea Instant deodorizing fibers and At least one of zinc shield fibers.
[0124] The Quick-drying cotton uses ultrasonic technology to evenly embed nano-scale porous mineral powder into the cotton cavity to produce cotton fibers with excellent quick-drying and UV resistance.
[0125] In the process of knitting the first yarn, the second yarn, and the third yarn, a single-sided large circular machine can be used. Optionally, a single-sided large circular machine with 28 needles / inch, a barrel diameter of 34 inches, and 72 routes can be used. In the process of knitting, the tension of each route can be controlled at 4.0cN~6.0cN, the horizontal density can be 30 longitudinal rows / inch~45 longitudinal rows / inch, and the vertical density can be 35 horizontal rows / inch~55 horizontal rows / inch to obtain the first deodorizing sub-fabric. The first deodorizing sub-fabric is a fabric with preliminary deodorizing function, which has antibacterial and deodorizing effects, but its ability to eliminate alkaline and acidic odors is slightly insufficient, so the first deodorizing sub-fabric needs to be subjected to post-finishing process treatment.
[0126] See also Figure 4 In some embodiments, the first deodorizing sub-fabric is subjected to a post-finishing process (step S80), comprising:
[0127] S81, adding the first deodorizing sub-fabric into the first finishing liquid to obtain a second deodorizing sub-fabric, wherein the first finishing liquid comprises tea polyphenols and chlorogenic acid;
[0128] S82, adding the second deodorizing sub-fabric into the second finishing liquid to obtain a third deodorizing sub-fabric, wherein the second finishing liquid includes at least one of a zinc finishing agent and a copper finishing agent; and performing a dehydration or drying treatment on the third deodorizing sub-fabric;
[0129] S83, performing a qualitative softening process on the third deodorizing sub-fabric after dehydration or drying to obtain a deodorizing fabric.
[0130] In this way, by utilizing chlorogenic acid, tea polyphenols and zinc or copper in the post-treatment process, the fabric not only has a deodorizing effect, but also has an effect on both alkaline and acidic odors. Tea polyphenols and their complexes also give the fabric a good anti-ultraviolet effect, and enhance the durability of deodorizing, anti-ultraviolet and other functions through the complexation between functional substances.
[0131] In the post-finishing process, the bath ratio of the first finishing liquid can be 1:15-1:30, the pH value of the bath liquid can be 5.5-6.5, and the treatment temperature can be 30-40° C. Within this range, the treatment efficiency of the first finishing liquid is higher.
[0132] Bath ratio refers to the ratio of bath liquid to fabric used to treat a certain amount of fabric during the dyeing or finishing process. A higher bath ratio allows the bath liquid to penetrate the fiber more fully, improving dyeing uniformity and finishing effects. A reasonable bath ratio can control costs and resource usage while ensuring dyeing or finishing quality.
[0133] Bath refers to a chemical solution used for dyeing or finishing. In the dyeing process, the bath contains dyes, additives, salts, etc., which are used to react the dyes with the fibers to achieve the dyeing effect. In the finishing process, the bath contains various chemicals, such as softeners, wrinkle-proof agents, shrink-proof agents, etc., which are used to give the fabric the desired properties and effects. The composition and ratio of the bath will affect the dyeing and finishing effects, such as color saturation, wrinkle resistance, softness, etc. The bath may include tea polyphenols, chlorogenic acid, cross-linking agents, penetrants, etc.
[0134] In certain embodiments, the concentration of tea polyphenols is 10.0 g / L to 25.0 g / L, and the concentration of chlorogenic acid is 10.0 g / L to 16.0 g / L.
[0135] For example, the concentration of tea polyphenols can be 10.0g / L~24.0g / L, 12.0g / L~24.0g / L, 15.0g / L~20.0g / L, 20.0g / L~25.0g / L, 15.0g / L~25.0g / L, etc.; the concentration of tea polyphenols can be 10.0g / L, 12.0g / L, 15.0g / L, 20.0g / L, 25.0g / L, etc.
[0136] The concentration of chlorogenic acid can be 10.0g / L~15.0g / L, 11.0g / L~15.0g / L, 12.0g / L~14.0g / L, 14.0g / L~16.0g / L, 12.0g / L~16.0g / L, etc.; the concentration of chlorogenic acid can be 10.0g / L, 11.0g / L, 12.0g / L, 14.0g / L, 16.0g / L, etc.
[0137] Within these parameter ranges, the fabric has the required functional properties and the overall uniformity of the fabric effect is good; in addition, the fabric production economy and sustainability are good.
[0138] Specifically, tea polyphenols are a type of natural polyphenol compound extracted from tea leaves, which has antioxidant, antibacterial, antistatic and other properties. In fabric finishing, tea polyphenols can be used as a functional additive to give fabrics antibacterial, antioxidant, antistatic and other properties, while also improving the softness and gloss of fabrics.
[0139] Chlorogenic acid is a natural phenolic acid compound found in many plants, including tea leaves and coffee beans. In fabric finishing, chlorogenic acid can be used as a softener and anti-wrinkle agent. It can improve the softness, feel and gloss of fabrics, and also has certain anti-wrinkle properties.
[0140] As functional additives, the effects of tea polyphenols and chlorogenic acid are usually related to their concentration. By controlling the concentration, the antibacterial, antioxidant, and softness properties of the fabric can be adjusted to meet specific functional requirements. Too high or too low concentrations of tea polyphenols and chlorogenic acid may result in uneven effects on the fabric. Therefore, controlling the concentration can ensure that the overall functionality and appearance of the fabric are consistent.
[0141] As additives, the dosage of tea polyphenols and chlorogenic acid is related to cost. Controlling the concentration can reasonably utilize and save the use of additives while meeting the functional requirements, so as to improve economy and sustainability.
[0142] Treatment temperature refers to the temperature conditions used in the dyeing or finishing process. Different dyes and chemicals have different requirements and adaptability to temperature. Appropriate treatment temperature can promote the reaction, diffusion and fixation of dyes or chemicals, and improve the dyeing and finishing effects. Too high or too low treatment temperature may lead to uneven dyeing, unsatisfactory effects or affect the performance of the fabric. Therefore, controlling the appropriate treatment temperature has a positive effect on the first finishing liquid to improve the deodorizing performance of the fabric.
[0143] In some embodiments, the bath solution may further include a cross-linking agent and a penetrant, wherein the cross-linking agent may be one of BTCA (1,2,3,4-tetracarboxylic acid butane), citric acid or maleic acid, and the concentration may be 10.0 g / L to 20.0 g / L; the penetrant may be at least one of JFC-1 and fast penetrant T, and the concentration may be 5.0 g / L to 10.0 g / L.
[0144] A cross-linking agent is a chemical substance that can form a cross-linked structure between the fibers of the deodorizing fabric to further enhance the deodorizing effect of the deodorizing fabric. After adding the cross-linking agent, under appropriate conditions (such as heat treatment or chemical treatment), the cross-linking agent reacts with the fibers to form stronger chemical bonds between the fibers, thereby improving the deodorizing performance, durability, wrinkle resistance, shrinkage resistance and pilling resistance of the fabric.
[0145] Penetrant is a substance with good penetration properties, which can help the bath liquid to better penetrate into the deodorizing fabric fiber to further enhance the deodorizing effect of the deodorizing fabric. Adding penetrant can increase the contact area between the bath liquid and the fiber, improve the treatment effect and uniformity. It helps other ingredients in the bath liquid to be more evenly distributed and adsorbed in the fabric fiber, thereby achieving a more consistent effect.
[0146] In some embodiments, in the post-finishing process, the rolling rate can be 65% to 80%, the pre-baking temperature can be 80° C. to 90° C., and the pre-baking time can be 3 minutes to 5 minutes. These parameters are related to the mechanical and thermal treatment of the fabric during the treatment process to enable the fabric to obtain better structural stability.
[0147] Roll-up rate refers to the dimensional change rate of fabric after compression or stretching during the finishing process. Specifically, the roll-up rate indicates the degree of shrinkage or elongation of the fabric size under certain force or stretching conditions. It is usually expressed as a percentage, with positive values indicating shrinkage and negative values indicating elongation. Adjustment of the roll-up rate can affect the dimensional stability and appearance of the fabric.
[0148] Pre-drying temperature refers to the temperature at which fabrics are pre-dried during the finishing process. Pre-drying temperature is usually used to remove moisture or volatile components from fabrics to achieve the effect of subsequent treatment steps. The selection of pre-drying temperature depends on the composition, structure and required treatment effect of the fabric, creating favorable conditions for further improving the deodorizing performance of the deodorizing fabric.
[0149] Pre-drying time refers to the time for pre-drying during the fabric finishing process. The pre-drying time is determined by the pre-drying temperature and the moisture content of the fabric, and it is very important to ensure that the fabric is fully dried. The length of the pre-drying time will affect the moisture content, softness, stability and subsequent treatment effect of the fabric, creating favorable conditions for further improving the deodorizing performance of the deodorizing fabric.
[0150] After the first deodorizing sub-fabric is finished with the first finishing liquid to obtain the second deodorizing sub-fabric, the second deodorizing sub-fabric needs to be further finished with the second finishing liquid to obtain the third deodorizing sub-fabric with better antibacterial and deodorizing properties.
[0151] The second finishing liquid may be an inorganic antibacterial finishing agent, such as a zinc finishing agent or a copper finishing agent. Zinc and copper have good antibacterial and deodorizing properties. They can inhibit the growth of bacteria and microorganisms and improve the deodorizing performance of deodorizing fabrics. In addition, zinc and copper are relatively environmentally friendly finishing agent options, and their impact on the environment during the treatment process is relatively small.
[0152] In certain embodiments, the zinc finishing agent includes at least one of zinc sulfate, zinc chloride, or zinc acetate, and the copper finishing agent includes at least one of copper ammonia solution, copper sulfate, or copper chloride.
[0153] Zinc sulfate, zinc chloride and zinc acetate are all water-soluble compounds that are easy to dissolve in the bath and are convenient to use in the finishing process. The copper ions in copper ammonia solution, copper sulfate and copper chloride are highly active and can form stable complexes with the fiber surface, which helps to improve the softness and antibacterial properties of the fabric. In addition, copper ions can react with the fiber surface to form a stable complex structure, improving the performance of the fiber, such as enhancing softness and improving wear resistance.
[0154] Specifically, the concentration of the zinc finishing agent and the copper finishing agent can be 10.0 g / L to 25.0 g / L, the finishing temperature can be 35° C. to 50° C., and the processing time can be 70 min to 90 min, so that the deodorizing fabric can obtain a better antibacterial effect.
[0155] Then, the third deodorizing sub-fabric is dehydrated to make the moisture content of the fabric 50% to 75%. Steam drying can be used, and the drying temperature can be 85°C to 105°C. The moisture content of the final product (i.e., the deodorizing fabric) can be 6.5% to 9.0%. Through the reaction, the hydroxyl groups and tea polyphenols on the fibers in the deodorizing fabric react with the carboxyl groups on the polycarboxylic acids and chlorogenic acid, and zinc or copper is used to form a complex with the polycarboxylic acids, chlorogenic acid, and tea polyphenols, thereby increasing the durability of the deodorizing function of the fabric.
[0156] Then, the third deodorizing sub-fabric is subjected to a shaping and softening process to finally obtain a deodorizing fabric. The shaping and softening process is intended to give the third deodorizing sub-fabric the desired shape stability and softness. The third deodorizing sub-fabric is heated under predetermined temperature and humidity conditions to rearrange the molecular structure inside the fibers in the third deodorizing sub-fabric to fix the shape and size of the third deodorizing sub-fabric. This helps the final deodorizing fabric to remain flat and not prone to wrinkling or deformation.
[0157] After shaping, the fabric is cooled to stabilize its shape. By rapidly lowering the temperature, the molecular structure of the fiber is fixed, allowing the third deodorizing sub-fabric to maintain the desired shape.
[0158] Then a softening treatment is performed, which is to increase the softness and comfort of the fabric. It can reduce the friction between fibers by applying softeners or other chemicals, thereby improving the softness and touch of the fabric. The softener used can be a mixture of Drymate hydrophilic softener, amino-modified dextran, polystyrene maleic anhydride sodium salt and water, and the mass ratio can be 8-12:3-8:2-5:100.
[0159] In the shaping and softening process, the temperature can be 125°C to 135°C, the running speed of the third deodorizing sub-fabric can be 20m / min to 30m / min, the overfeed rate can be 10% to 13%, and the shaping and softening process time can be 3 to 7 minutes.
[0160] The deodorizing fabric according to the embodiment of the present invention is prepared by the preparation method of the deodorizing fabric according to any of the above embodiments.
[0161] The deodorizing fabric of the embodiment of the present invention has preliminary antibacterial and deodorizing effects by using yarn with antibacterial and deodorizing functions. Furthermore, in the subsequent post-finishing process, the antibacterial and deodorizing effects of the deodorizing fabric are further improved. In addition, in the post-finishing process, the deodorizing fabric has anti-ultraviolet effect, high stability, softness, wear resistance, etc.
[0162] Example 1
[0163] In this embodiment, the deodorizing fabric is prepared by the following method:
[0164] Commercially available activated clay and titanium dioxide are used as raw materials, mixed evenly in a mass ratio of 2:1 to obtain a solid mixture, dispersed in a mass ratio of the solid mixture to deionized water of 1:3, and 1.0% of a dispersant, 0.5% of a thickener, and 1.0% of a defoaming agent (to the mass fraction of the entire first dispersed system) are added to prepare a first dispersed system.
[0165] Under the condition of water circulation cooling (temperature is 10°C), the powder is ground and dispersed by a sand mill to a particle size of D90=1.656 μm to obtain a second dispersion system with a falling ball viscosity of 20s, and adjusted to neutral for standby use. The dispersant is sodium naphthalenesulfonate, the thickener is sodium hydroxyethyl cellulose, and the defoamer model is ZY-T6911 defoamer.
[0166] Cellulose pulp is used as raw material, and cellulose sulfonate is prepared through a viscose preparation process. In the cellulose sulfonate dissolution step, a denaturant is added with a content of 2.0 wt% of methyl cellulose, and the denaturant is polyethylene glycol (model PEG-1500). After mixing and other viscose preparation processes, a cellulose spinning solution is prepared. In the cellulose spinning solution, the mass fraction of methyl cellulose is 8.86%, the mass fraction of sodium hydroxide is 6.21%, the falling ball viscosity is 76s, and the maturity (10% NH 4 Cl value) is 20mL, the degree of esterification of viscose is 58, and the sulfur content of viscose is 2.25%.
[0167] The prepared second dispersion system and pore former are added to the cellulose spinning stock solution at a mass ratio of 8.0% of the solid mixture to the type A cellulose and 5.0% of the pore former to the type A cellulose to obtain a blended spinning stock solution. The pore former is sodium carbonate.
[0168] The blended spinning solution is spun through an adjusted coagulation bath, and the primary filament bundle is drawn to obtain a formed filament bundle, which is drawn, cut, and subjected to a mild desulfurization process, an oiling process, a drying process, and finally a loosening process to obtain a deodorizing fiber.
[0169] In the coagulation bath, the concentration of sulfuric acid is 95g / L, the concentration of sodium sulfate is 290g / L, the concentration of aluminum sulfate is 12.5g / L, and the temperature is 50°C; in the desulfurization bath, Na 2 SO 3 The concentration of the deodorizing fiber is 6.0 g / L and the temperature is 85°C; in the oiling process, the concentration of the oil bath is 3.0 g / L and the temperature is 70°C. Then, steam drying is adopted at a drying temperature of 110°C, and the moisture regain of the deodorizing fiber after drying is 12%.
[0170] The deodorizing fibers were prepared according to a certain mass ratio. In the cotton opening and combing processes, the beater speed was set to 720rpm / min, and the cotton plucking machine operating efficiency was set to 92%; the sliver delivery speed was 55m / min, and the sliver basis weight was 16g / 5m.
[0171] In the drawing process, two passes are adopted, the first drawing: the number of roots combined is 8, and the total drafting multiple is 8.1 times; the second drawing: the number of roots combined is 7, and the total drafting multiple is 7.6 times; in the coarse yarn process, the roller spacing is 10mm*26mm*36mm, the total drafting multiple is 8.7 times, the twist coefficient is 70, and the yarn CV is 4.9%; in the fine yarn process, the roller spacing is 17mm*38mm, the total drafting multiple is 25 times, the twist is 80 twists / 10cm, and the twist coefficient is 360.
[0172] According to the above process, according to the deodorizing fiber and The instant deodorizing fibers are mixed evenly in a mass ratio of 40%:60% to obtain a first yarn; the nylon 6 staple fibers and the antibacterial cotton fibers are mixed evenly in a mass ratio of 40%:60% to obtain a second yarn; The quick-drying cotton and the polylactic acid fiber are mixed evenly in a mass ratio of 50%:50% to obtain a third yarn. Among them, the antibacterial cotton fiber is Chitosan antibacterial cotton.
[0173] Then, a single-sided large circular knitting machine with a machine gauge of 28 needles / inch, a barrel diameter of 34 inches, and 72 routes is used to prepare the first deodorizing sub-fabric. Every 12 routes are a cycle, and the cycle mode is arbitrary. The first yarn is used in the 1st / 4th / 5th / 7th / 9th / 10th route, and the coil length is 30cm / 100 coils; the second yarn is used in the 2nd / 8th / 11th route, and the coil length is 30cm / 100 coils; the third yarn is used in the 3rd / 6th / 12th route, and the coil length is 30cm / 100 coils; the tension of each route is controlled at 6.0cN, the horizontal density is 30 longitudinal rows / inch, and the longitudinal density is 35 horizontal rows / inch.
[0174] The prepared first deodorizing sub-fabric is further subjected to a post-finishing process to obtain a second deodorizing sub-fabric. In the first finishing liquid of the post-finishing process, the bath ratio is 1:15, the pH value of the bath liquid is 5.5, and the treatment temperature is 40°C.
[0175] In the bath liquid, the concentration of tea polyphenols is 10.0 g / L, the concentration of chlorogenic acid is 10.0 g / L; the cross-linking agent is BTCA, the concentration is 10.0 g / L; the penetrant is JFC-1, the concentration is 5.0 g / L.
[0176] In the post-finishing process, the rolling rate is 65%, the pre-baking temperature is 50°C, and the pre-baking time is 5 minutes; then, the second deodorizing sub-fabric is finished in the second finishing liquid to obtain a third deodorizing sub-fabric. The second finishing liquid is a zinc finishing agent, the zinc finishing agent is zinc sulfate, the concentration is 10.0g / L, the processing temperature is 50°C, and the processing time is 70 minutes. Then, the third deodorizing sub-fabric is dehydrated to a moisture content of 50%. Steam is used for drying, the drying temperature is 85°C, and the moisture content of the final product is 9.0%.
[0177] Then, the third deodorizing sub-fabric is subjected to a shaping and softening process to finally obtain a deodorizing fabric. In the shaping and softening process, the temperature is 125°C, the running speed of the third deodorizing sub-fabric is 20 m / min, the overfeed rate is 13%, the softener used is a mixture of Drymate hydrophilic softener, amino-modified dextran, polystyrene maleic anhydride sodium salt and water, the mass ratio of which is 8:3:2:100, and the shaping and softening process time is 7 minutes.
[0178] In this embodiment, the deodorizing fabric has an inhibition rate of 89.3% on Staphylococcus aureus, 90.8% on Escherichia coli, and 87.1% on Candida albicans; the mildew resistance level can reach Level 1; its ammonia reduction rate is 89.1%, the trimethylamine reduction rate is 86.5%, and the isovaleric acid reduction rate is 89.3%; the ultraviolet protection factor is 60; the drip diffusion time is 2.8s, and the evaporation rate is 0.19g / h.
[0179] Example 2
[0180] In this embodiment, the deodorizing fabric is prepared by the following method:
[0181] Commercially available activated clay and titanium dioxide are used as raw materials, mixed evenly in a mass ratio of 3:1 to obtain a solid mixture, dispersed in a mass ratio of the solid mixture to deionized water of 1:4, and 1.5% of a dispersant, 1.0% of a thickener, and 1.8% of a defoaming agent (to the mass fraction of the entire first dispersed system) are added to prepare a first dispersed system.
[0182] Under the condition of water circulation cooling (temperature is 15°C), the sand mill is used for grinding and dispersion, and the particle size is ground to D90=1.357μm to obtain a second dispersion system, whose falling ball viscosity is 28s, and adjusted to neutral for standby use. The dispersant is sodium dodecylbenzene sulfonate, the thickener is sodium carboxymethyl cellulose, and the defoamer model is ZY-F609 high temperature resistant defoamer.
[0183] Cellulose pulp is used as a raw material, and cellulose sulfonate is prepared through a viscose preparation process. In the cellulose sulfonate dissolution step, a denaturant with a cellulose methyl content of 3.0 wt% is added, and the denaturant is a fatty alcohol polyoxyethylene ether. After mixing and other viscose preparation processes, a cellulose spinning solution is prepared. In the cellulose spinning solution, the mass fraction of cellulose methyl is 8.93%, the mass fraction of sodium hydroxide is 6.75%, the falling ball viscosity is 95s, and the maturity (10% NH 4 Cl value) is 26.5mL, the degree of viscose esterification is 71, and the sulfur content of viscose is 2.38%.
[0184] The prepared second dispersion system and pore former are added to the cellulose spinning stock solution at a mass ratio of 11.5% of the solid mixture to the type A cellulose and 7.2% of the pore former to the type A cellulose to obtain a blended spinning stock solution. The pore former is sodium bicarbonate.
[0185] The blended spinning solution is spun through an adjusted coagulation bath, and the primary filament bundle is drawn to obtain a formed filament bundle, which is drawn, cut, and subjected to a mild desulfurization process, an oiling process, a drying process, and finally a loosening process to obtain a deodorizing fiber.
[0186] In the coagulation bath, the concentration of sulfuric acid is 103.5 g / L, the concentration of sodium sulfate is 310.6 g / L, the concentration of aluminum sulfate is 14.1 g / L, and the temperature is 47.2 °C; in the desulfurization bath, Na 2 SO 3 The concentration of the deodorizing fiber is 8.0 g / L and the temperature is 72°C; in the oiling process, the concentration of the oil bath is 4.3 g / L and the temperature is 60°C. Then, steam drying is adopted at a drying temperature of 122°C, and the moisture regain of the deodorizing fiber after drying is 10.3%.
[0187] The deodorizing fibers were prepared according to a certain mass ratio. In the cotton opening and combing processes, the beater speed was set to 810rpm / min, and the plucking machine operating efficiency was set to 93.5%; the sliver delivery speed was 60m / min, and the sliver basis weight was 14g / 5m.
[0188] In the drawing process, two passes are adopted, the first drawing: the number of roots combined is 8, and the total drafting multiple is 8.5 times; the second drawing: the number of roots combined is 7, and the total drafting multiple is 7.8 times; in the coarse yarn process, the roller spacing is 10mm*26mm*36mm, the total drafting multiple is 8.85 times, the twist coefficient is 75, and the yarn CV is 4.46%; in the fine yarn process, the roller spacing is 17mm*38mm, the total drafting multiple is 30 times, the twist is 90 twists / 10cm, and the twist coefficient is 375.
[0189] According to the above process, according to the deodorizing fiber and The instant deodorizing fibers are mixed evenly at a mass ratio of 45%:55% to obtain a first yarn; the nylon 66 staple fibers and the antibacterial cotton fibers are mixed evenly at a mass ratio of 35%:65% to obtain a second yarn; The quick-drying cotton and the polylactic acid fiber are mixed evenly in a mass ratio of 55%:45% to obtain a third yarn. Among them, the antibacterial cotton fiber is Chitosan antibacterial cotton.
[0190] Then, a single-sided large circular knitting machine with a machine gauge of 28 needles / inch, a barrel diameter of 34 inches, and 72 routes is used to prepare the first deodorizing sub-fabric. Every 12 routes are a cycle, and the cycle mode is arbitrary. The 1st / 4th / 5th / 7th / 9th / 10th routes use the first yarn, and the coil length is 21cm / 100 coils; the 2nd / 8th / 11th routes use the second yarn, and the coil length is 21cm / 100 coils; the 3rd / 6th / 12th routes use the third yarn, and the coil length is 21cm / 100 coils; the tension of each route is controlled at 5.0cN, the horizontal density is 36 longitudinal rows / inch, and the longitudinal density is 45 horizontal rows / inch.
[0191] The prepared first deodorizing sub-fabric is further subjected to a post-finishing process to obtain a second deodorizing sub-fabric. In the first finishing liquid of the post-finishing process, the bath ratio is 1:25, the pH value of the bath liquid is 6.0, and the treatment temperature is 35°C.
[0192] In the bath liquid, the concentration of tea polyphenols is 20.2 g / L, the concentration of chlorogenic acid is 13.5 g / L; the cross-linking agent is citric acid, the concentration is 15.6 g / L; the penetrant is fast penetrant T, the concentration is 7.6 g / L.
[0193] In the post-finishing process, the rolling rate is 72.6%, the pre-drying temperature is 76°C, and the pre-drying time is 4 minutes; then, the second deodorizing sub-fabric is finished in the second finishing liquid to obtain a third deodorizing sub-fabric. The second finishing liquid is a zinc finishing agent, the zinc finishing agent is zinc acetate, the concentration is 17.8g / L, the processing temperature is 43°C, and the processing time is 80 minutes. Then, the third deodorizing sub-fabric is dehydrated to a moisture content of 66%. Steam is used for drying, the drying temperature is 95°C, and the moisture content of the final product is 7.9%.
[0194] Then, the third deodorizing sub-fabric is subjected to a shaping and softening process to finally obtain a deodorizing fabric. In the shaping and softening process, the temperature is 130°C, the running speed of the third deodorizing sub-fabric is 25 m / min, the overfeed rate is 11.8%, the softener used is a mixture of Drymate hydrophilic softener, amino-modified dextran, polystyrene maleic anhydride sodium salt and water, the mass ratio of which is 10:5:3.5:100, and the shaping and softening process time is 5 minutes.
[0195] In this embodiment, the deodorizing fabric has an inhibition rate of 91.0% on Staphylococcus aureus, 91.3% on Escherichia coli, and 88.3% on Candida albicans; the mildew resistance level can reach Level 1; its ammonia reduction rate is 90.5%, the trimethylamine reduction rate is 88.0%, and the isovaleric acid reduction rate is 91.1%; the ultraviolet protection factor is 71; the drip diffusion time is 2.6s, and the evaporation rate is 0.21g / h.
[0196] Example 3
[0197] In this embodiment, the deodorizing fabric is prepared by the following method:
[0198] Commercially available activated clay and titanium dioxide are used as raw materials, mixed evenly in a mass ratio of 4:1 to obtain a solid mixture, dispersed in a mass ratio of the solid mixture to deionized water of 1:5, and 2.0% of a dispersant, 1.5% of a thickener, and 2.5% of a defoaming agent (to the mass fraction of the entire first dispersed system) are added to prepare a first dispersed system.
[0199] Under the condition of water circulation cooling (temperature is 20°C), the sand mill is used for grinding and dispersion, and the particle size is ground to D90=1.217μm to obtain the second dispersion system, whose falling ball viscosity is 35s, and adjusted to neutral for standby use. The dispersant is sodium hexametaphosphate, the thickener is sodium carboxyethyl cellulose, and the defoamer model is ZY-T69113 silicone polyether defoamer.
[0200] Cellulose pulp is used as raw material, and cellulose sulfonate is prepared through a viscose preparation process. In the cellulose sulfonate dissolution step, a denaturant with a cellulose methyl content of 3.5 wt% is added, and the denaturant is a fatty amine polyoxyethylene ether. After mixing and other viscose preparation processes, a cellulose spinning solution is prepared. In the cellulose spinning solution, the mass fraction of cellulose methyl is 9.55%, the mass fraction of sodium hydroxide is 7.10%, the falling ball viscosity is 115s, and the maturity (10% NH 4 Cl value) is 32mL, the degree of viscose esterification is 82, and the sulfur content of viscose is 2.61%.
[0201] The prepared second dispersion system and pore-forming agent are added to the cellulose spinning stock solution at a mass ratio of 15% of the solid mixture to the type A cellulose and 8.0% of the pore-forming agent to the type A cellulose to obtain a blended spinning stock solution. The pore-forming agent is sodium carbonate.
[0202] The blended spinning solution is spun through an adjusted coagulation bath, and the primary filament bundle is drawn to obtain a formed filament bundle, which is drawn, cut, and subjected to a mild desulfurization process, an oiling process, a drying process, and finally a loosening process to obtain a deodorizing fiber.
[0203] In the coagulation bath, the concentration of sulfuric acid is 110g / L, the concentration of sodium sulfate is 330g / L, the concentration of aluminum sulfate is 16.5g / L, and the temperature is 45°C; in the desulfurization bath, Na 2 SO 3 The concentration of the deodorizing fiber is 9.5 g / L and the temperature is 60°C; in the oiling process, the concentration of the oil bath is 5.5 g / L and the temperature is 50°C. Then, steam drying is adopted at a drying temperature of 130°C, and the moisture regain of the deodorizing fiber after drying is 12%.
[0204] The deodorizing fibers were prepared according to a certain mass ratio. In the cotton opening and combing processes, the beater speed was set at 880rpm / min, and the plucking machine operating efficiency was set at 95%; the sliver delivery speed was 65m / min, and the sliver weight was 12g / 5m.
[0205] In the drawing process, two passes are adopted, the first drawing: the number of roots combined is 8, and the total drafting multiple is 8.8 times; the second drawing: the number of roots combined is 7, and the total drafting multiple is 8.1 times; in the coarse yarn process, the roller spacing is 10mm*26mm*36mm, the total drafting multiple is 9.0 times, the twist coefficient is 80, and the yarn CV is 4.3%; in the fine yarn process, the roller spacing is 17mm*38mm, the total drafting multiple is 35 times, the twist is 100 twists / 10cm, and the twist coefficient is 398.
[0206] According to the above process, according to the deodorizing fiber and The instant deodorizing fibers are mixed evenly at a mass ratio of 50%:50% to obtain a first yarn; the nylon 6 staple fibers and the antibacterial cotton fibers are mixed evenly at a mass ratio of 30%:70% to obtain a second yarn; The quick-drying cotton and the polylactic acid fiber are mixed evenly in a mass ratio of 60%:40% to obtain a third yarn. Among them, the antibacterial cotton fiber is Zinc shield fiber.
[0207] Then, a single-sided large circular knitting machine with a machine gauge of 28 needles / inch, a barrel diameter of 34 inches, and 72 routes is used to prepare the first deodorizing sub-fabric. Every 12 routes are a cycle, and the cycle mode is arbitrary. The 1st / 4th / 5th / 7th / 9th / 10th routes use the first yarn, and the coil length is 15cm / 100 coils; the 2nd / 8th / 11th routes use the second yarn, and the coil length is 15cm / 100 coils; the 3rd / 6th / 12th routes use the third yarn, and the coil length is 15cm / 100 coils; the tension of each route is controlled at 4.0cN, the horizontal density is 45 longitudinal rows / inch, and the longitudinal density is 55 horizontal rows / inch.
[0208] The prepared first deodorizing sub-fabric is further subjected to a post-finishing process to obtain a second deodorizing sub-fabric. In the first finishing liquid of the post-finishing process, the bath ratio is 1:30, the pH value of the bath liquid is 6.5, and the treatment temperature is 30°C.
[0209] In the bath liquid, the concentration of tea polyphenols is 25.0 g / L, the concentration of chlorogenic acid is 16.0 g / L; the cross-linking agent is maleic acid, the concentration is 20.0 g / L; the penetrant is JFC-1, the concentration is 10.0 g / L.
[0210] In the post-finishing process, the rolling rate is 80%, the pre-baking temperature is 90°C, and the pre-baking time is 3 minutes; then, the second deodorizing sub-fabric is finished in the second finishing liquid to obtain a third deodorizing sub-fabric. The second finishing liquid is a copper finishing agent, and the copper finishing agent is a copper ammonia solution with a concentration of 25.0g / L, a processing temperature of 35°C, and a processing time of 90 minutes. Then, the third deodorizing sub-fabric is dehydrated to a moisture content of 75%. Steam is used for drying, and the drying temperature is 105°C. The moisture content of the final product is 6.5%.
[0211] Then, the third deodorizing sub-fabric is subjected to a shaping and softening process to finally obtain a deodorizing fabric. In the shaping and softening process, the temperature is 135°C, the running speed of the third deodorizing sub-fabric is 30 m / min, the overfeed rate is 10%, the softener used is a mixture of Drymate hydrophilic softener, amino-modified dextran, polystyrene maleic anhydride sodium salt and water, the mass ratio of which is 12:8:5:100, and the shaping and softening process time is 3 minutes.
[0212] In this embodiment, the deodorizing fabric has an inhibition rate of 92.9% on Staphylococcus aureus, 93.5% on Escherichia coli, and 90.5% on Candida albicans; the mildew resistance level can reach level 0; its ammonia reduction rate is 92.1%, trimethylamine reduction rate is 90.2%, and isovaleric acid reduction rate is 93.0%; the ultraviolet protection factor is 85; the drip diffusion time is 2.3s, and the evaporation rate is 0.24g / h.
[0213] Comparative Example 1
[0214] On the basis of Example 3, during the preparation process of the deodorizing fiber, activated clay was not used to modify the deodorizing fiber, and other conditions were the same as those in Example 3.
[0215] In this comparative example, the deodorizing fabric has an inhibition rate of 88.7% on Staphylococcus aureus, 89.3% on Escherichia coli, and 88.1% on Candida albicans; the mildew resistance level can reach Level 1; its ammonia reduction rate is 87.7%, trimethylamine reduction rate is 86.8%, and isovaleric acid reduction rate is 88.0%; the ultraviolet protection factor is 71; the drip diffusion time is 2.9s, and the evaporation rate is 0.16g / h.
[0216] Comparative Example 2
[0217] On the basis of Example 3, during the preparation process of the deodorizing fiber, no pore-forming agent is used to modify the deodorizing fiber, and other conditions are the same as those in Example 3.
[0218] In this comparative example, the deodorizing fabric has an inhibition rate of 86.0% on Staphylococcus aureus, 86.5% on Escherichia coli, and 86.3% on Candida albicans; the mildew resistance level can reach Level 1; its ammonia reduction rate is 85.7%, trimethylamine reduction rate is 85.1%, and isovaleric acid reduction rate is 86.2%; the ultraviolet protection factor is 65; the drip diffusion time is 2.7s, and the evaporation rate is 0.17g / h.
[0219] Comparative Example 3
[0220] On the basis of Example 3, the first deodorizing sub-fabric is not subjected to post-finishing, and other conditions are the same as those in Example 3.
[0221] In this comparative example, the deodorizing fabric has an inhibition rate of 82.1% on Staphylococcus aureus, 83.0% on Escherichia coli, and 82.6% on Candida albicans; the mildew resistance level can reach Level 2; its ammonia reduction rate is 81.3%, trimethylamine reduction rate is 80.9%, and isovaleric acid reduction rate is 80.1%; the ultraviolet protection factor is 56; the drip diffusion time is 2.7s, and the evaporation rate is 0.16g / h.
[0222] In the description of this specification, the description with reference to the terms "one embodiment", "certain embodiments", "illustrative embodiments", "examples", "specific examples", or "some examples" means that the specific features, structures, materials, or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials, or characteristics described may be combined in any one or more embodiments or examples in a suitable manner.
[0223] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the claims and their equivalents.
Claims
1. A method for preparing a deodorizing fiber, characterized in that: The method comprises: Providing activated clay and titanium dioxide, and mixing the activated clay and the titanium dioxide in a mass ratio of 2:1 to 4:1 to obtain a solid mixture; Dispersing the solid mixture with deionized water in a mass ratio of 1:3 to 1:5, and adding a dispersant, a thickener and a defoamer to obtain a first dispersed system; Grinding the first dispersion system to a particle size of D90≤1.656 μm to obtain a second dispersion system; Providing a cellulose spinning solution and a pore-forming agent, and adding the second dispersed system and the pore-forming agent to the cellulose spinning solution to obtain a blended spinning solution; The blended spinning solution is introduced into a coagulation bath for spinning and forming to obtain deodorizing fibers.
2. The method for preparing the deodorizing fiber according to claim 1, characterized in that: In the first dispersed system, the mass fraction of the dispersant is 1.0% to 2.0%, the mass fraction of the thickener is 0.5% to 1.5%, and the mass fraction of the defoaming agent is 1.0% to 2.5%.
3. The method for preparing the deodorizing fiber according to claim 1, characterized in that: The dispersant includes at least one of sodium naphthalenesulfonate, sodium dodecylbenzenesulfonate or sodium hexametaphosphate.
4. The method for preparing the deodorizing fiber according to claim 1, characterized in that: The thickener includes at least one of sodium hydroxyethyl cellulose, sodium carboxymethyl cellulose, sodium carboxyethyl cellulose or hydroxypropyl methyl cellulose.
5. The method for preparing the deodorizing fiber according to claim 1, characterized in that: Calculated by mass fraction, the cellulose spinning stock solution comprises 8.86% to 9.55% of methyl cellulose and 6.21% to 7.10% of sodium hydroxide.
6. The method for preparing the deodorizing fiber according to claim 5, characterized in that: The mass fraction of the solid mixture to the methyl cellulose is 8.0% to 15.0%, and the mass fraction of the pore-forming agent to the methyl cellulose is 5.0% to 8.0%.
7. The method for preparing the deodorizing fiber according to claim 1, characterized in that: The cellulose spinning solution is prepared by the following steps: Providing cellulose sulfonates; The cellulose sulfonate is dissolved, and in the process of dissolving the cellulose sulfonate, a denaturant accounting for 2.0 wt% to 3.5 wt% of the cellulose methyl content is added to obtain the cellulose spinning stock solution.
8. The method for preparing the deodorizing fiber according to claim 7, characterized in that: The denaturant includes at least one of polyethylene glycol, fatty alcohol polyoxyethylene ether or fatty amine polyoxyethylene ether.
9. The method for preparing the deodorizing fiber according to claim 1, characterized in that: The concentration of sulfuric acid in the coagulation bath is 95 g / L to 110 g / L, the concentration of sodium sulfate is 290 g / L to 330 g / L, and the concentration of aluminum sulfate is 12.5 g / L to 16.5 g / L.
10. A deodorizing fiber, characterized in that: The deodorizing fiber is prepared by the preparation method of the deodorizing fiber according to any one of claims 1 to 9.
11. A method for preparing a deodorizing fabric, characterized in that: The method comprises: providing a first yarn, a second yarn, and a third yarn, wherein the first yarn comprises the deodorizing fiber of claim 10; The first yarn, the second yarn and the third yarn are knitted into a plurality of knitted structures, each of the knitted structures has 12 loops as a cycle, wherein the first yarn is used in the first, fourth, fifth, seventh, ninth and tenth loops, the second yarn is used in the second, eighth and eleventh loops, and the third yarn is used in the third, sixth and twelfth loops, and the coil lengths of the first yarn, the second yarn and the third yarn are all 15 cm / 100 loops to 30 cm / 100 loops, so as to obtain a first deodorizing sub-fabric; The first deodorizing sub-fabric is subjected to a post-finishing process to obtain the deodorizing fabric.
12. The method for preparing the deodorizing fabric according to claim 11, characterized in that: The post-finishing process of the first deodorizing sub-fabric comprises: adding the first deodorizing sub-fabric into a first finishing liquid to obtain a second deodorizing sub-fabric, wherein the first finishing liquid comprises tea polyphenols and chlorogenic acid; adding the second deodorizing sub-fabric into a second finishing liquid to obtain a third deodorizing sub-fabric, wherein the second finishing liquid comprises at least one of a zinc finishing agent or a copper finishing agent; Dehydrating or drying the third deodorizing sub-fabric; The deodorizing sub-fabric is subjected to a qualitative softening process after being dehydrated or dried to obtain the deodorizing fabric.
13. The method for preparing the deodorizing fabric according to claim 12, characterized in that: The concentration of the tea polyphenols is 10.0 g / L to 25.0 g / L, and the concentration of the chlorogenic acid is 10.0 g / L to 16.0 g / L.
14. The method for preparing the deodorizing fabric according to claim 12, characterized in that: The zinc finishing agent includes at least one of zinc sulfate, zinc chloride or zinc acetate, and the copper finishing agent includes at least one of copper ammonia solution, copper sulfate or copper chloride.
15. A deodorizing fabric, characterized in that: The deodorizing fabric is prepared by the preparation method of the deodorizing fabric according to any one of claims 11 to 14.
Citation Information
Patent Citations
Preparation of environment-friendly type antibiotic and odor removing textile
CN101324027A
Antibacterial, anti-mite and deodorizing adhesive fiber and preparation method thereof
CN110230112A
Antibacterial, deodorizing, skin-care and health-care cellulose fiber and preparation method thereof
CN114182379A
Cool fabric, spinning method and application
CN115366495A